Ameliorative Effect of Zinc Oxide Nanoparticles on Antioxidants and Sperm Characteristics in Streptozotocin-Induced Diabetic Rat Testes. (25th October 2015) - Afifi, Mohamed; Almaghrabi, Omar A.; Kadasa, Naif Mohammed
Abstract : The present study investigated the impact of zinc oxide nanoparticles (ZnONPs) on the oxidative status and sperm characteristics in diabetic rat testicular tissue. Forty male albino rats were used in this study; 10 of them served as a control and 30 rats were injected with a single dose (100 mg/kg) of streptozotocin intraperitoneally. They were subdivided into diabetic, diabetic + ZnONPs (10 mg/kg B.W.), and diabetic and cotreated with ZnONPs + insulin groups. The sperm count and motility were assessed. The activity and mRNA expression of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GRD), and Glutathion-S-Transferase (GST) were determined in the testicular tissue. Malondialdehyde (MDA) and reduced glutathione (GSH) levels were estimated in the testicular tissue. Sperm count and motility increased in ZnONPs treated diabetic rats. A significant increase in the activity and mRNA expression of SOD, CAT, GPx, GRD, and GST was shown in ZnONPs treated diabetic rats. MDA significantly decreased, while GSH increased in testicular tissue of ZnONPs treated diabetic rats. It was concluded that ZnONPs either alone or in combination with insulin have the ability to increase the sperm count and motility and protect the testicular tissue against the oxidative stress induced by diabetes in rats.